The Next Generation of Agriculture - Minton, Ernest J. (My University, 2025)
This informal report to the Kansas Legislature summarizes the wide-ranging impact of K-State Research and Extension in 2025, highlighting initiatives in agriculture, environmental stewardship, public health, and community development across Kansas.
RPT116_2025_01
Keywords: RPT116; Administrative and Research Reports; legislature